From Village to Globe: A Dynamic Real-Time Map of African Fields Through PlantVillage - Kehs, Annalyse; McCloskey, Peter; Chelal, John; Morr, Derek; Amakove, Stellah; Plimo, Bismark; Mayieka, John; Ntango, Gladys; Nyongesa, Kelvin; Pamba, Lawrence; Jeptoo, Melodine; Mugo, James; et al. (Frontiers in Sustainable Food Systems, 2021)
A major bottleneck to the application of machine learning tools to satellite data of African farms is the lack of high-quality ground truth data. Here we describe a high throughput method using youth in Kenya that results in a cost-effective method for high-quality data in near real-time. This data is presented to the global community, as a public good and is linked to other data sources that will inform our understanding of crop stress, particularly in the context of climate change.